Association between Localized Scleroderma Cutaneous Assessment Tool and clinicopathologic characteristics in patients with morphea - Yıldız Gürsel Ürün; Elif Usturalı Keskin (Galenos Publishing House, 2022)
Background and Design: Morphea is also known as localized scleroderma. It is a rare autoimmune skin disease characterized by inflammation and sclerosis in the dermis and sometimes in the subcutaneous tissue. Laboratory findings, imaging, and histopathological features facilitate diagnosis and provide sufficient information about disease severity. Clinicopathologic correlations and severity factors in morphea are poorly described. Thus, this study aimed to review the clinical and histopathological features and treatment responses of patients with morphea and compare these features with disease activity and damage scores to identify new tools for assessing disease severity other than clinical findings. The applicability of the Localized Scleroderma Cutaneous Assessment Tool in clinical practice was also evaluated. Materials and Methods: This study reviewed data of 41 patients who had a histopathologically confirmed diagnosis of morphea and had been followed up regularly for at least 6 months. The modified Localized Scleroderma Skin Severity Index (mLoSSI), Localized Scleroderma Skin Damage Index (LoSDI), Physician Global Assessment-Activity (PGA-A), and Physician Global Assessment-Damage (PGA-D) were calculated at baseline and final treatment. Results: Among morphea subtypes, superficial morphea had significantly more sclerosis in the papillary dermis and plaque-type morphea had significantly more sclerosis in the reticular dermis (p<0.05). When positive antinuclear antibody (ANA) and high levels of thyroid autoantibodies were compared with mLoSSI, LoSDI, PGA-A, and PGA-D scores at baseline, no significant correlation was found. Comparison of the subgroups according to the initial mLoSSI and LoSDI scores revealed no significant histopathological differences between the groups. Conclusion: Although the mLoSSI, LoSDI, PGA-A, and PGA-D scores can be successfully used for the follow-up and treatment of patients with morphea, no correlation was found between positive ANA, high levels of thyroid autoantibodies, and histopathological features.